2023
DOI: 10.1021/acsomega.3c02222
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of High-Entropy Alloys with a Tailored Composition and Phase Structure Based on Thermodynamic Parameters and Film Thickness Using a Novel Combinatorial Target

Abstract: This study presents a novel synthesis route for high-entropy alloys (HEAs) and high-entropy metallic glass (HEMG) using radio frequency (RF) magnetron sputtering and controlling the HEA phase selection according to atomic size difference (δ) and film thickness. The preparation of HEAs using sputtering requires either multitargets or the preparation of a target containing at least five distinct elements. In developing HEA-preparation techniques, the emergence of a novel sputtering target system is promising to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The patterns confirmed the amorphous structure of the thin films grown under WHT conditions and a minor crystalline structure of the annealed thin films. These results demonstrated that a more crystalline structure could be synthesized using the proposed target configuration based on a combination of refractory elements, as previously reported. , The diffraction data and calculated VECs are summarized in Table , indicating that the prepared thin films exhibited dual-phase FCC and BCC as well as single FCC structures. The planes (111), (222), and (200) corresponded to the FCC structure, whereas (200), (211), (310), (222), and (330) were attributable to the BCC structure.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The patterns confirmed the amorphous structure of the thin films grown under WHT conditions and a minor crystalline structure of the annealed thin films. These results demonstrated that a more crystalline structure could be synthesized using the proposed target configuration based on a combination of refractory elements, as previously reported. , The diffraction data and calculated VECs are summarized in Table , indicating that the prepared thin films exhibited dual-phase FCC and BCC as well as single FCC structures. The planes (111), (222), and (200) corresponded to the FCC structure, whereas (200), (211), (310), (222), and (330) were attributable to the BCC structure.…”
Section: Resultsmentioning
confidence: 97%
“…This process involved the simultaneous arrangement of 20 pieces, as shown in Figure a, which were then combined into a single target configuration using a ceramic screw. This innovative approach led to the development of a novel target system, enabling the customization of alloy compositions to meet the specific requirements of various applications requiring HEAs, as demonstrated previously . Furthermore, the precise positioning of each constituent element and the total number of elements played key roles in ensuring a consistent alloy composition.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation